ANALISIS NILAI PERUSAHAAN JASA SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Yudhi Prabowo, - (2019)
This research was conducted to test the influence of the capital structure, growth and profitability of firm value. Doing research on the company's Sub Sector transportation which listed on the Indonesia Stock Exchange as a sample. The technique of determination of the sample using the method of purposive sampling (purposive sampling method). The selection of the sample of 35 company Sub Sector transportation were listed on the Indonesia Stock Exchange in 2014-2017 produce company 14 is acceptable. Data analysis is done using the Microsoft Excel 2010 and hypothesis testing in this study using a Panel Data Regression Analysis with the program E-Views 9.0 and the level of significance of 5%. The results of the test were obtained (1) Capital structure is represented by DER no effect significantly positife to the firm value, (2) Growth is represented by GROWTH effect significantly positife to the firm value, (3) the profitability is represented by ROE no effect significantly positife to the firm value.